2cos2x-√3=0 ; √2x-1=x-2 ; √2x+1=x-1 ; √3x+1=x-3 ; √x+1=1-x

2cos2x-√3=0 ; √2x-1=x-2 ; √2x+1=x-1 ; √3x+1=x-3 ; √x+1=1-x
Гость
Ответ(ы) на вопрос:
Гость
1) cos2x=√3/2 2x=+-arccos(√3/2)+2πn, n∈Z 2x=+- π/6+2πn, n∈Z x=+-π/12+πn, n∈Z 2) (√2x-1)²=(x-2)², x-2≥0 2x-1=x²-4x+4 x²-6x+5=0 D/4=9-5=4, √4=2 x₁=3+2=5,  x₂=3-2=1 x₂=1 - не удовлетворяет -(x-2)≥0 ответ: х=5 3) (√2х+1)²=(х-1)², х-1≥0 2х+1=х²-2х+1 х²-4х=0, х(х-4)=0 х₁=0, х=4 х₁=0 не удовлетворяет условию х-1≥0 ответ: х=4 4) (√3х+1)²=(х-3)², х-3≥0 3х+1=х²-6х+9 х²-9х+8=0 D=81-32=49, √49=7 x₁=(9+7)/4=4 x₂=(9-7)/4=0.5, не удовлетворяет условию ответ: х=4 5) (√х+1)²=(1-х)², 1-х≥0 х+1=1-2х+х² х²-3х=0, х(х-3)=0 х₁=0, х₂=3- не удовлетворяет условию ответ: х=0
Не нашли ответ?
Ответить на вопрос
Похожие вопросы